Biomass accumulation and response to defoliation of seven fodder shrubs on arid environments - Beltrán-López, Sergio; Urrutia-Morales, Jorge; Loredo-Osti, Catarina; Velázquez-Martínez, Mauricio (Ecosistemas y Recursos Agropecuarios, 2025)
With the objective of evaluating forage accumulation and the response to defoliation of forage shrubs in arid areas, biomass accumulation, elongation rate and regrowth capacity were evaluated in the chamizo species (Atriplex canescens, Pursh, Nutt.), ramoncillo (Dalea bicolor, Willd), mariola (Parthenium incanum, Kunth), vara dulce (Eysenhardtia polystachya, Ort. Sarg), escobilla (Buddleja scordioides, Kunth), guajillo (Acacia berlandieri, Benth) and cenizo (Atriplex nummularia, Lindl) subjected to three cutting intensities based on the height of the plants (low: 25%, medium: 50% and high: 75%). The elongation rate was different between species (P < 0.001), but not between cutting intensities (P > 0.05); chamizo and vara dulce were the species that showed the greatest growth. Biomass accumulation was different between species and between cutting intensities (P < 0.0001). The average daily biomass accumulation was 3.39 ± 5.0 g day-1, increasing as the cutting intensity increased, with chamizo being the species that accumulated the most biomass in the high cutting intensity with 14.6 ± 2.34 g day-1. It is concluded that the regrowth capacity was similar in all species of forage shrubs, but the accumulation of biomass depended on both the species and the cutting intensity.